Climax [videorecording (DVD)] - Noé, Gaspar, 1963-; Noé, Gaspar, 1963-; Boutella, Sofia, 1982-; Guillermic, Romain; Yacoub, Souheila (Lionsgate, 2019)
When several French dancers gathered for a rehearsal in a remote location discover that their drinks have been laced with LSD, the evening descends into violence and chaos.